Factores sociales y epidemiológicos y su relación con el cumplimiento del control prenatal. - Márquez Jiménez, Rosmery Beatriz (2018)
The prenatal control, it is one of the fundamental pillars on which maternal health is based, and is an important measure to evaluate the progress of pregnancy. The present research work was of a cross-sectional descriptive type, and the identification and analysis of the social and epidemiological factors related to the fulfillment of the prenatal control, whose information was obtained through a survey, applied to pregnant women from of the six months of gestation of the Health Center Nº1 in the Canton of Loja; the results show which are the main factors that are related to the fulfillment of the prenatal control on the part of the pregnant women, within the social factors it was identified that more than 50% are of civil status Free Union, followed by single and married, with respect to coexistence 76% live with husband and children, in a lower percentage with parents; Likewise, 86% of pregnant women surveyed do receive family support while the remaining percentage does not receive it; Regarding epidemiological factors, it was evident that 82% of pregnant women had their first prenatal control in the first trimester of pregnancy, while less than a quarter of them performed their first prenatal check-up in the second trimester of pregnancy. The number of prenatal checkups showed that 82% of pregnant women had 3 or more prenatal check-ups, complying with the minimum number of prenatal check-ups as established by the MSP, accessing maternal care services in a timely and early manner of the Health Center. Keywords: Prenatal Control, Pregnant, Factors